2019
DOI: 10.1037/pspa0000158
|View full text |Cite
|
Sign up to set email alerts
|

When mere action versus inaction leads to robust preference change.

Abstract: for assistance with data collection; Fabienne Voncken, Simke van Oijen and Sjors van de Schoot for creating the candy images; Xin Gao, Haokui Xu and members of the Food Choice on Impulse lab for helpful comments on earlier versions of the manuscript. The data of Experiments 1 and 2 have been reported in a master thesis by Linda Schmale at the University of Amsterdam. The data of Experiments 5 and 6 have been reported in bachelor theses by Roos Greven and Evert Palm at Radboud University. The data of Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 68 publications
(179 reference statements)
5
76
5
Order By: Relevance
“…This approach‐healthy association might attach greater value to healthy food cues, resulting in greater choice of healthy food. Indeed, studies have found that participants chose to consume healthy foods more often when those participants were trained to respond to healthy food items without responding to other items. In short, although we did not find evidence for a main effect of approach/avoidance training on eating behaviour, some evidence suggests that approach/avoidance training focused on approach of healthy food might be an effective means of increasing the relative consumption of healthy food to unhealthy food.…”
Section: Discussionmentioning
confidence: 99%
“…This approach‐healthy association might attach greater value to healthy food cues, resulting in greater choice of healthy food. Indeed, studies have found that participants chose to consume healthy foods more often when those participants were trained to respond to healthy food items without responding to other items. In short, although we did not find evidence for a main effect of approach/avoidance training on eating behaviour, some evidence suggests that approach/avoidance training focused on approach of healthy food might be an effective means of increasing the relative consumption of healthy food to unhealthy food.…”
Section: Discussionmentioning
confidence: 99%
“…There were no visual or formal outliers to test for robustness of the model. We were also interested whether the effect of the training would differ for different choice reaction times, as previous research has observed that the choice effect becomes weaker the more time participants take (Chen et al, 2019). However, although the coefficient was negative, reaction times were not a significant predictor of app choice χ 2 = .2.23, p = .135.…”
Section: Confirmatorymentioning
confidence: 99%
“…Furthermore, we have substantially increased the amount of measurements we collect from each participant (e.g., they make many food choices) and moved from between-subjects to within-subjects designs when possible. By applying such procedures, we are able to consistently find effects of executing or withholding simple motor responses on food evaluation (e.g., Chen, Veling, Dijksterhuis, & Holland, 2016; and choice (Chen et al, 2019). A challenge for future work is to develop reliable experimental procedures for other outcomes than food evaluation or choice (e.g., food intake or weight loss), which can further contribute to evaluating the evidential value of ICT.…”
Section: Health Psychology Reviewmentioning
confidence: 99%
“…In our lab we recently conducted a series of seven preregistered well-powered experiments where we assessed effects of the go/no-go training, a widely used inhibitory control training, on food choice (Chen, Holland, Quandt, Dijksterhuis, & Veling, 2019). The aim of this research project was to obtain a high-quality data set of effects of go/no-go training on food choice.…”
mentioning
confidence: 99%
See 1 more Smart Citation